PENGARUH KOMPENSASI DAN STRESS KERJA TERHADAP PERPUTARAN KARYAWAN PT. MENARA MAS MEGA MANDIRI - Philip Willie; Alfonsius Alfonsius; Chon Cho Reynols Manday (STIE-PMCI, 2019)
Abstract. The success and progress of a company is strongly influenced by the human resources within the company. Generally employees who have worked for a long time will certainly understand more about how to work in a company and do their work better than the newly received employees, so to get good employees needed good compensation in return for what they do and also must be able to control work stress that occurs in the company so that employees will feel ease. The purpose of this study was to determine the influence of compensation and work stress on employee turnover at PT. Menara Mas Mega Mandiri.This study uses a type of quantitative analysis. The sampling technique uses a saturated sampling technique with a population of 40 sales employees. The data analysis technique is using multiple linear regression.Simultaneously there is a significant influence between compensation and work stress variables on employee turnover but partially shows that compensation does not influence employee turnover while partially there is an influence of work stress on employee turnover of PT. Menara Mas Mega Mandiri.Â Key Words : Compensation, Work Stress , Employee Turnover.Â